The Algiers Motel Incident - Hersey, John, 1914-1993 (Book collections on Project MUSE., 2019)
"In July 1967, on the third night of a race riot, Detroit police raided the Algiers Motel, a black-owned business located about a mile from the epicenter of the unrest. The police responded to a report of sniper fire from the motel and proceeded to round up its occupants. They beat them and threatened to kill them. Three black men were killed that night, and no one was convicted for their deaths. First published in 1968, John Hersey's book strings together interviews, police reports, court testimony, and news reports to give an account of the events and their aftermath."--Provided by publisher